Secoxyloganin inhibits growth of breast cancer MDA-MB-231 cells via induction of apoptosis and cell cycle arrest - Jie Ma; Cong Peng (All Life)
This study was set to study the anti-proliferative effects of secoxyloganin in MDA-MB-231 breast cancer cells. The MTT cell viability assay results demonstrated that secoxyloganin significantly (p < 0.05) inhibited the growth of the MDA-MB-231 cells with an IC50 of 6.5 μM which was significantly (p < 0.05) lower than the IC50 of 38 μM against the normal fR2 cells. Unveiling of molecular mechanism revealed that secoxyloganin disrupted the DNA integrity of MDA-MB-231 cells and triggered apoptosis. Annexin V/PI staining revealed that the percentage of apoptotic MDA-MB-231 cells increased from 3.7% in control to 40.2% at 24 μM of secoxyloganin. This was accompanied by an enhancement of Bax, and suppression of Bcl-2. The effects of secoxyloganin on the distribution of cells in various cell cycle phases was also assessed. The results showed the proportion of cells in the G0/G1 phase increased from 32.76% in control to 77.50% at 24 μM of secoxyloganin suggesting G0/G1 cell cycle arrest. This was also associated with suppression of cyclin D2 expression. Taken together, these findings demonstrate the anticancer properties of secoxyloganin through cell cycle arrest and apoptosis.